Pilot study to assess the likely impact of the free movement of labour in the CSME on the OECS labour market : final report - Watson, Noel (A-Z Information Jamaica Limited [S.l.], 2007)
Reports on the nature, extent and possible impact on OECS economies of the free movement of persons in the CSME.